PLAN DE GESTIÓN Y SU INCIDENCIA EN EL DESARROLLO TURÍSTICO DE LOS HABITANTES DE LA PARROQUIA ANGOCHAGUA, CIUDAD DE IBARRA, AÑO 2022. - Reinado Salvatierra, Rosmery Ruby (2022)
The objective of this work is to analyze a management plan for tourism development in the Angochagua parish, thus being an opportunity to sustainably take advantage of the diversity of tourist attractions offered by the Angochagua parish for the benefit of the population and improvement of your quality of life. For this I used the method: documentary analysis and structured observations, which allowed me to analyze the situation in Angochagua and be able to contribute to its development with my project. Currently, tourism in Ecuador represents one of the main sources of income, thus helping the economic, environmental and sociocultural growth of each population that is dedicated to tourism. The Angochagua Parish is characterized by its beautiful natural and cultural attractions of great value, its main economic activity is agriculture carried out by men and the very typical hand embroidery carried out by the women of this community. Each of these attractions have been very attractive for national and international tourists who contribute with their visit to the growth and development of this parish